Legal Protection for Auction Winners of Liability against Transition of Land Rights Certificates - Marliyanti Praja Kusuma; Sri Kusriyah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
In this journal the author has two objectives in this research, first, To find out and analyze the legal protection of the auction winner of mortgage rights in the transfer of land rights certificates and To find out and analyze the legal position of the transfer of land rights certificates for the auction winners in the construction of legal certainty. The approach method in this research is normative juridical where this research provides a detailed, systematic and comprehensive description in which the author examines and studies the norms contained in the legislation. The research specification is a descriptive analysis that is limited to efforts to reveal a problem or situation or event as it is, so that it is merely revealing facts. The data required includes primary data, secondary data, and tertiary data. Taken by data collection method, data analysis method using qualitative approach, namely understanding the data through collecting, filtering, analyzing and making conclusions on the data obtained throughout the research systematically. Based on the research, it can be concluded that legal protection for legitimate auction winners is still difficult in practice. The existence of disputes and lawsuits from land owners does not provide legal certainty of the status of the auction object being sold where buyers who have good intentions participate in the auction process and have fulfilled their obligations but sometimes cannot immediately enjoy the goods purchased. Although the acquisition of the object of the auction in the form of a Mortgage object is in accordance with the procedural and legally valid, however, the administrative requirements at the Land Office cannot be carried out due to the status quo.